Satuan Lalu Lintas Polrestabes Makassar: Memastikan Keselamatan di Jalan Raya dengan Komunikasi Persuasif - Amrullah, M Ishak Fauzan; Andriansyah, Andriansyah (Journal of Communication Sciences (JCoS), 2023)
The problem of traffic accidents and the consequences of these accidents has become a social problem today. The Security and Safety Unit of the Makassar Police Traffic Unit in this case as a Government Organization in charge of securing and regulating traffic uses Public Service Announcements to reduce the number of traffic accidents, especially in Makassar City. The purpose of this research is to find out the role of persuasive communication and the supporting factors and inhibiting factors experienced by the Security and Safety Unit of the Makassar Police Traffic Unit in reducing traffic accidents. The research method used is qualitative research with a descriptive approach consisting of observation, interview and observation. The results showed that the Makassar Police had applied persuasive communication principles well such as Reciprocity, Commitment and Consistency, Social Proof, Authority and Liking. The Liking principle still needs to be improved and the Scarcity principle is not used because it is considered not in accordance with the objectives of persuasive communication carried out by the Makassar Police. Supporting factors that can reduce traffic accidents are people who obey traffic rules, orderly, operation of billboard installation locations in accident-prone or strategic areas, attractive banner designs, posts on social media for millennials and attractive billboard designs and COVID-19 cases. Inhibiting factors in reducing traffic accidents such as motorists who are not careful, the small size of billboards so that they are not visible to motorists, lack of public awareness of traffic signs, road and weather factors.